Valproic acid metabolites inhibit dihydrolipoyl dehydrogenase activity leading to impaired 2-oxoglutarate-driven oxidative phosphorylation - Luis, Paula B. M. (2015)
The effect of the antiepileptic drug valproic acid (VPA) on mitochondrial oxidative phosphorylation (OXPHOS) was investigated in vitro. Two experimental approaches were used, in the presence of selected respiratory-chain Substrates: (1) formation of ATP i